Spirituality and the practice of health care - Robinson, Simon (Palgrave Macmillan, 2003)
Spiritual aspects of care are becoming increasingly, important to many nurses. This is part of a growing emphasis on holistic, patient-focused care, and enhancement of patients' quality of life. In this book, the authors explore discuss and analyse a practical definition of spirituality in relation to modern healthcare, and invite the reader to consider the key elements of spirituality in terms of conceptual, practical and organisational themes. Vignettes and case studies play a central role in encouraging the reader to take a reflective stance in which the themes of the book can be applied to practice